Understanding suicide terrorism : psychosocial dynamics - Kumar, Updesh; Mandal, Manas K. (New Delhi : SAGE, 2016)
The is a comprehensive compilation of articles by experts in the field of suicide terrorism from across the world and across disciplines with a focus on suicide missions. It provides an insightful perspective on suicide terror as a phenomenon and as a process, and suggests psychosocial pathways for understanding the enigma that suicide terror poses.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 22, 2016).
Keywords: Terrorism -- Psychological aspects; Terrorists -- Suicidal behavior; Suicide bombers; Suicide bombings